2021
DOI: 10.1039/d0ra08652e
|View full text |Cite
|
Sign up to set email alerts
|

Probing the activity of transition metal M and heteroatom N4 co-doped in vacancy fullerene (M–N4–C64, M = Fe, Co, and Ni) towards the oxygen reduction reaction by density functional theory

Abstract: In this study, a novel type oxygen reduction reaction (ORR) electrocatalyst is explored using density functional theory (DFT); the catalyst consists of transition metal M and heteroatom N4 co-doped in vacancy fullerene (M–N4–C64, M = Fe, Co, and Ni).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The number of coordinated nitrogen atoms varying from 1 to 6 can be modeled using graphene edges 36,37 or defective graphene. 38–42 Besides graphene as the substrate to host the M–N site, other graphitic carbon structures are also considered, such as CNTs, 43–46 fullerenes, 47–49 graphyne 50,51 and graphdiyne. 52–54 The unique properties ( e.g.…”
Section: Modeled Structures and Computational Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of coordinated nitrogen atoms varying from 1 to 6 can be modeled using graphene edges 36,37 or defective graphene. 38–42 Besides graphene as the substrate to host the M–N site, other graphitic carbon structures are also considered, such as CNTs, 43–46 fullerenes, 47–49 graphyne 50,51 and graphdiyne. 52–54 The unique properties ( e.g.…”
Section: Modeled Structures and Computational Approachesmentioning
confidence: 99%
“…The number of coordinated nitrogen atoms varying from 1 to 6 can be modeled using graphene edges 36,37 or defective graphene. [38][39][40][41][42] Besides graphene as the substrate to host the M-N site, other graphitic carbon structures are also considered, such as CNTs, [43][44][45][46] fullerenes, [47][48][49] graphyne 50,51 and graphdiyne. [52][53][54] The unique properties (e.g., local curvature, sp/sp 2 hybridized porous structure) provided by those allotropes can contribute to the enhancement of the catalytic reactivities.…”
Section: Overview Of Well-explored Structuresmentioning
confidence: 99%
“…An ideal 2e – ORR electrocatalyst demands neither too strong nor too weak bonding strength between active sites and oxygen species to preserve the O–O bond. , Therefore, a catalyst platform with a flexibly tailorable electronic structure is crucial for modulating the ORR pathway and boosting the desired kinetic process. , Thanks to the maximum atomic utilization and adjustable coordination structure, single-atom catalysts (SACs) may provide a promising platform to flexibly manipulate the ORR pathway. Recently, it has been demonstrated that introducing heteroatom (O, B, S, P, etc.) into the Fe/Co/Ni–N–C single-metal site can engineer the local environment of single-metal active site toward the desired 2e – ORR. , However, these heteroatom doping strategies cause the problems of demetallation and stability issues of single-metal sites under harsh operating conditions. , Even worse, the dissociative metal ions, especially iron and cobalt ions, will potentially lead to the decomposition of H 2 O 2 due to the Fenton effect. Different from the heteroatom doping strategy, tailoring the coordination number of M–N sites offers another intriguing approach to simultaneously regulate the electronic structure and maintain the robust stability of SACs. , Actually, it is found that engineering the local coordination number of atomically dispersed M–N x moieties can greatly promote the reaction activity. However, the local coordination number modulation on the metal–N sites, which could mediate the 2e – /4e – ORR pathways, remains challenging and has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, RuN 4 doped carbon matrixes have been reported in theory and experiment to be promising ORR electrocatalysts. [40][41][42] Moreover, theoretically prediction shows that in the composite materials such as single atom Co decorated porphyrinlike porous fullerene (Co-C 24 N 24 ) [43] or Fe-N 4 embedded vacant fullerene (Fe-N 4 -C 64 ), [44] the metal atom is the main catalytic activity center for ORR, and catalyzes through a more effective four-electron pathway.…”
Section: Introductionmentioning
confidence: 99%